Research Progress on Photosensitizers for DSSC - Carella, Antonio; Borbone, Fabio; Centore, Roberto (Frontiers in Chemistry, 2018)
Dye sensitized solar cells (DSSC) are considered one of the most promising photovoltaic technologies as an alternative to traditional silicon-based solar cells, for their compatibility with low-cost production methods, their peculiar optical and mechanical properties and the high indoor efficiency. Photosensitizers represent one of the most important components of a DSSC device and probably the most thoroughly investigated in the last twenty years, with thousands of dyes that have been proposed and tested for this kind of application. In this review we aimed to provide an overview of the three main classes of DSSC photosensitizers, namely ruthenium(II) polypyridyl complexes, Zn-porphyrin derivatives and metal-free organic dyes. After a brief introduction about the architecture and operational principles of a DSSC and the state of the art of the other main components of this type of device, we focused our discussion on photosensitizers. We have defined the numerous requirements DSSC photosensitizers should satisfy and have provided an overview of their historical development over the years; by examining specific dyes reported in the literature, we attempted to highlight the molecular design strategies that have been established for the optimization of their performance in real devices both in terms of efficiency (which recently reaches an outstanding 14.3%) and operational stability. Finally, we discussed, in the last section, the possible future developments of this intriguing technology.